Bio-mechanisms of swimming and flying. Fluid dynamics, biomimetic robots, and sports science (Springer, 2008)
Biomechanics studies of animals in swimming and flying can serve an increasing role in understanding the mechanisms that enable animals to move effectively and efficiently in fluid, as well as analyzing the characteristics of their various forms of behavior in fluid.